2021
DOI: 10.3389/fnins.2021.554194
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Stimulation Modulates Resting-State Functional Connectivity in Unresponsive Wakefulness Syndrome Patients

Abstract: Passive listening to music is associated with several psychological and physical benefits in both, healthy and diseased populations. In this fMRI study, we examined whether preferred music has effects on the functional connectivity within resting-state networks related to consciousness. Thirteen patients in unresponsive wakefulness syndrome (UWS) and 18 healthy controls (HC) were enrolled. Both groups were exposed to different auditory stimulation (scanner noise, preferred music, and aversive auditory stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
(36 reference statements)
1
12
1
Order By: Relevance
“…Third, the studies reported quantitative or mixed quantitative and qualitative data. Studies were excluded if they did not meet one or more of the aforementioned criteria (see e.g., [22,28,30,[42][43][44][45][46]).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Third, the studies reported quantitative or mixed quantitative and qualitative data. Studies were excluded if they did not meet one or more of the aforementioned criteria (see e.g., [22,28,30,[42][43][44][45][46]).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Boltzmann et al [28] exposed 13 UWS patients to two stimulation conditions, one consisting of a preferred music compilation and the other consisting of an aversive auditory stimulation. The two stimulation conditions and scanner noise, each lasting 8 min, were presented in a random order across patients.…”
Section: Studies Assessing the Impact Of Recorded Musicmentioning
confidence: 99%
See 2 more Smart Citations
“…Verbal stories/messages mainly involve the narration/recalling of meaningful events the patient had previously experienced and/or the description of the current situation with a positive perspective for recovery and future [28,35,36]. The use of such an intervention strategy is supported by the view that (a) the emotional content of the stories/messages can activate limbic and paralimbic structures of the brain (see above) [37][38][39], (b) the calling of the patient's name can promote forms of behavioral or nonbehavioral (physiological) responses of alertness and attention [31,40], and (c) the overall narration can constitute a useful form of auditory stimulation, that is, beneficial input for a sensory channel, which is generally well preserved in this population [26,41].…”
Section: Introductionmentioning
confidence: 99%